2017
DOI: 10.1073/pnas.1608357114
|View full text |Cite
|
Sign up to set email alerts
|

Flowering phenology shifts in response to biodiversity loss

Abstract: Observational studies and experimental evidence agree that rising global temperatures have altered plant phenology-the timing of life events, such as flowering, germination, and leaf-out. Other large-scale global environmental changes, such as nitrogen deposition and altered precipitation regimes, have also been linked to changes in flowering times. Despite our increased understanding of how abiotic factors influence plant phenology, we know very little about how biotic interactions can affect flowering times,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
91
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(97 citation statements)
references
References 41 publications
3
91
3
Order By: Relevance
“…Diversity level appears to have no significant effect on either leaf‐out or flowering dates in models where abiotic and biotic effects were considered together. The positive correlation between increasing soil TN and later leaf‐out date is consistent with previous studies (Wolf et al., ). This may be because the TN favors root growth over shoot growth (Nord & Lynch, ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Diversity level appears to have no significant effect on either leaf‐out or flowering dates in models where abiotic and biotic effects were considered together. The positive correlation between increasing soil TN and later leaf‐out date is consistent with previous studies (Wolf et al., ). This may be because the TN favors root growth over shoot growth (Nord & Lynch, ).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, previous work has found that warming experiments could underestimate plant phenological responses to climate change (Wolkovich et al., ). Our findings indicate that shifts in community diversity and plant composition may account for some of this difference because warming experiments that occur over short time scales are unlikely to capture the full effects of community shifts (Wolf et al., ).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…; Körner and Basler ), biodiversity loss (Wolf et al. ), extreme weather events (Rich et al. ; Jentsch et al.…”
Section: Introductionmentioning
confidence: 99%